Profil Psikologis Atlet Pencak Silat Kota Kupang Dalam Menghadapi Pertandingan - Lani, Melsin Apredi Suhelna Mellu; Anakaka, Dian L.; Ratu, Feronika (Jurnal Global Ilmiah, 2025)
Sports psychology is a subfield of psychology that studies human behavior in sports. Pencak Silat, an Indonesian cultural tradition, is believed to have existed since prehistoric times and remains popular today. This study examined Pencak Silat athletes in Kupang to determine their psychological profile in competition. The methodology employed was descriptive qualitative research with an interactive analysis approach based on Miles and Huberman. The study revealed that self-confidence promotes positive thinking, while motivation is divided into intrinsic and extrinsic motivation. Uncontrolled anxiety can impair performance. Concentration plays a crucial role in focusing and executing strategies during competition. Factors that positively influence the psychological profile of Pencak Silat athletes in Kupang include support from close individuals, particularly training partners, coaches, and family.